Strengths and Interests Between Actors in Collaborative Governance: Review of the Riverside Settlement Revitalization Policy in Banjarmasin City - Muhammad Noor; Falih Suaedi; Antun Mardiyanta (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2023)
This study aims to analyze and identify the strengths and interests of state actors and non-state actors in the revitalization of residents’ houses in the riverside area of Banjarmasin City from the perspective of Collaborative Governance. This study used a qualitative approach by collecting data through observation, in-depth analysis, and document analysis. The findings of this study explain that collaborative governance is an alternative to public policy as an interactive process involving state and non-state actors autonomously who use shared rules and norms carried out collectively to solve societal problems. Collaboration involving actors in power with interests in decision-making might fail during its implementation. This research contributes to the scientific literature on interactions between actors and collaborative governance because the problems faced by the public are fought for, and collaborative governance implementation cannot be separated from the presence of actors involved in advocating for issues of public concern.